2017
DOI: 10.1016/j.nbd.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of motor proteins, axonal transport deficits and adult-onset neurodegenerative diseases

Abstract: Neurons affected in a wide variety of unrelated adult-onset neurodegenerative diseases (AONDs) typically exhibit a “dying back” pattern of degeneration, which is characterized by early deficits in synaptic function and neuritic pathology long before neuronal cell death. Consistent with this observation, multiple unrelated AONDs including Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and several motor neuron diseases feature early alterations in kinase-based signaling pathways associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(142 citation statements)
references
References 176 publications
4
123
0
Order By: Relevance
“…Subsequently, APP containing vesicles must be delivered at specific neuronal domains, a process that is mediated by phosphorylation‐dependent mechanisms that regulate the molecular motors (Morfini et al . , ; Brady & Morfini ). Interestingly, it has been reported that aberrant regulation of molecular motors by phosphorylation‐dependent mechanisms contributes to the loss of synaptic connectivity (Pigino et al .…”
Section: App Extracellular Domainmentioning
confidence: 98%
See 2 more Smart Citations
“…Subsequently, APP containing vesicles must be delivered at specific neuronal domains, a process that is mediated by phosphorylation‐dependent mechanisms that regulate the molecular motors (Morfini et al . , ; Brady & Morfini ). Interestingly, it has been reported that aberrant regulation of molecular motors by phosphorylation‐dependent mechanisms contributes to the loss of synaptic connectivity (Pigino et al .…”
Section: App Extracellular Domainmentioning
confidence: 98%
“…; Deyts et al . ; Brady & Morfini ). In this context, targeting of APP at specific plasma membrane domains such as the GC relies on particular trafficking and sorting mechanisms characteristic of different population of neurons (Brunholz et al .…”
Section: App Extracellular Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, formation of ADF/cofilin-actin filament bundles (rods) that can occlude neurites and block vesicle transport has been implicated in neurodegenerative diseases [95]. In addition to these changes in cytoskeletal structures, accumulation of toxic disease proteins can lead to defects in axonal transport [96101]. For example, defective axonal transport was reported to be a key early feature of pathogenesis prior to neurodegeneration in various SOD1 animal models of ALS [102106].…”
Section: Protein Toxicity In the Cytoplasmmentioning
confidence: 99%
“…Brady and co-workers (46, 47) have developed a unifying hypothesis to explain neurodegenerative diseases including Alzheimer's, Parkinson's, Huntington's, and prion diseases as follows. 1) Aggregated proteins stimulate the activity of kinases.…”
Section: Discussionmentioning
confidence: 99%